Modeling of the transport and deposition of polydispersed particles: Effects of hydrodynamics and spatiotemporal evolution of the deposition rate. (June 2018) - Ma, Enze; Ouahbi, Tariq; Wang, Huaqing; Ahfir, Nasre-Dine; Alem, Abdellah; Hammadi, Ahmed
Abstract: A time-distance-dependent deposition model is built to investigate the effects of hydrodynamic forces on the transport and deposition of polydispersed particles and the evolution of deposition rates with time and distance. Straining and the heterogeneity of the particle population are considered to play important roles in the decreasing distribution of deposition rates. Numerical simulations were applied in a series of sand column experiments at different fluid velocities for three different porous media. The effects of hydrodynamics forces are elaborated with the systematic variations of deposition dynamic parameters of the proposed model. With retention distributions with particle size as well as temporal and spatial evolutions of deposition rates, the transport and deposition mechanisms of polydispersed particles will be elucidated through the interplay of the variation of the particle size distribution of mobile particle populations and the geometrical change of the porous medium due to retention (straining and blocking). Graphical abstract: Image 1 Highlights: Model of transport and fate of polydispersed particles is proposed. Colloid filtration theory underestimates pore constriction deposition. Deposition mechanisms vary with evolution of particle population size. Interplay of particle PSD and pore network structure determines deposition rate.